Anatomical Analysis of Graft Compatibility in Some Almond ScionRootstock Combination - Yeşim Okay; Başak Özdemir; Ajlan Yılmaz; Hatice Nurhan Büyükkartal (Journal of Agricultural Sciences)
In this study, graft compatibility between almond cultivar Lauranne and almond seedling and Rootpac R, Rootpac 90, Rootpac 70 and Rootpac 40 clonal rootstocks was anatomically investigated. The anatomical analysis of scion/ rootstock combinations was performed by taking cross sections for 30 days and 12 months after T-budding in June, 2017. It was determined that, 30 days after grafting, the callus cells developed but cambial continuity has not occurred between the rootstock and scion tissues in all scion/rootstock combinations. 12 months after grafting, cambial relation was established, vascular differentiation was observed, regular parenchymatic tissue properties and scleroid (petrosal cell) cells and sclerenchyma bundles were seen in the graft union. There was no problem in terms of rootstock- scion compatibility in Lauranne almond cultivar which was grafted on almond seedling and some Rootpac clonal rootstocks.